The Effects of Textual Input Enhancement and Inputflooding on the Comprehension and Retention of Macro/ Micro Discourse Markers Functions among Iraqi University EFL Students - Salih, Sana’Khalifa (Journal of Tikrit University for Humanities, 2023)
Discourse markers (DMs) are essential for improving the quality of speaking and writing as well as increasing comprehension of spoken and written text. This research aims at investigating the effects of two techniques (textual input enhancement and inputflooding) on students’ comprehension and retention of macro/ micro discourse markers functions. 96 EFL University students were randomly chosen from a population of 120 students. The study subjects were split into two experimental groups and one control group and they took part in 8 sessions to teach them L2 DMs, by using two techniques, i.e., textual input enhancement and inputflooding. The students are tested before and after the sessions by the comprehension test of DMs functions. The outcomes showed that all two experimental groups did better than the control group in their post-tests. Moreover, the findings indicated a significant difference in the comprehension test between the two experimental groups in favour of the textual input enhancement group. Moreover, the performance of the Textual Enhancement group on the DMs Posttest is somewhat close to its performance in the retention test. On the other hand, the statistically significant effect of the inputflooding technique on the DMs Posttest is greater than its effect on the retention test. It is recommended to use input enhancement techniques to help the EFL students to master L2 materials effectively.